Pengembangan Aplikasi Forum dan Informasi Kegiatan Majelis Taklim DKI Jakarta Berbasis Android - Mochamad Apri Utama; Ester Lumba (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to provide an alternative to the management and Congregation of Islamic Board in managing, disseminating, and searching for information on the activities of the Islamic Board in the DKI Jakarta area as well as a place of discussion between the Assembly and their congregation in the form of an application system. The search and dissemination of this information requires an internet connection in order to determine and see the location of activities that are connected from Google Maps. Board Managers who disseminate information on activities and congregations who see. The method in developing this application uses the Rational Unified Process (RUP) and Unified Modeling Language (UML) to create an application model design. This application development was designed using PHP, Java, and XML programming languages ​​and database management using MySQL. Research conducted using these methods resulted in an application forum and information on Android-based Islamic Board activities. The results of this study are the application of the forum as well as information on the activities of the Jakarta-based Islamic Board in Jakarta based on Black Box and User Acceptance Testing.